Computational simulation of transfer and dispersion of automobile transport exhaust gases by the airflow over the urban quarter territory - Boyarshinov, Mikhail Gennadievich; Balabanov, Denis Sergeevich (Computational Continuum Mechanics, 2011)
To describe the concentration fields of automobile exhaust gases in the city atmospheric air, the system of Euler differential equations (continuity, motion, energy, and state) in partial derivatives with appropriate boundary conditions is used. The numerical solution is based on the large-particle method (Davydov’s method). The computational experiment allows us to determine the distribution of the main gas-dynamic characteristics of a gas-air mixture flow and the distribution of concentration of carbon monoxide that is a common constituent of the exhaust gas over a complex spatial area.